Integrated Public Health Strategies for Vector Control in the Context of Climate Change and Urbanization - Umar, Fadly (Yayasan Sinergi Kawula Muda, 2023)
Climate change and urbanization are reshaping the epidemiology of vector-borne diseases, leading to increased transmission risks in densely populated areas. This study systematically reviews the impact of urban expansion, rising temperatures, and erratic precipitation patterns on vector habitats and disease proliferation. A comprehensive literature search was conducted in PubMed, Scopus, and Google Scholar, selecting studies published within the last 20 years that empirically examine climate change and urbanization’s role in vector ecology. Findings highlight that rapid urbanization creates ideal breeding environments for disease vectors, exacerbating public health challenges. The urban heat island effect intensifies vector survival, while inadequate waste and water management promote their proliferation. Climate variability alters seasonal disease transmission, extending vector activity periods and increasing epidemic occurrences. Emerging technologies such as IoT and GIS have shown promise in improving surveillance and disease management but require policy support and infrastructure investments for optimal effectiveness. Mitigating these risks necessitates integrated approaches, incorporating urban planning, climate adaptation, and enhanced vector control strategies. Strengthening community participation, expanding access to sanitation, and developing predictive modeling frameworks will be essential in managing disease risks. Future research should explore adaptive control measures and long-term vector resistance mechanisms to inform sustainable public health interventions.